Pendekatan Pendekatan Sosial Budaya dalam Membentuk Konseling yang Inklusif dan Efektif di SMAN 7 Tasikmalaya - Indi oktavialista; Feida Noor Laila Isti’adah; Zulfa Ma'aly Zhafirah; Rahma Aulia; Rasya Ahmad Tripasca; Najwa Fatimah Azzahra; Agna Ghaisan Syazani; Tina Agustin (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The socio-cultural approach is a crucial aspect of creating inclusive and relevant guidance and counseling services, particularly at SMAN 7 Tasikmalaya, which has a diverse student background. This study aims to understand how socio-cultural values are integrated into the counseling process to help students address various issues, such as adaptation difficulties, social gaps, and interpersonal conflicts. Using a qualitative research method with a case study approach, data were collected through in-depth interviews, observations of counseling activities, and document analysis. The results indicate that implementing strategies such as classical guidance, home visits, and community-based approaches effectively strengthens the relationship between counselors and students and enhances students' skills in dealing with differences. Additionally, the integration of local culture into counseling programs positively impacts fostering mutual understanding among students. The implications of this study highlight the need for counselor training to better comprehend students' socio-cultural contexts, enabling counseling services to be designed according to their needs and conditions. This research contributes significantly to developing guidance models that respect socio-cultural diversity in educational settings.